POTENTIAL CONTRIBUTION OF REVERSE LOGISTICS TO RESTAURANTS - Dutra, Ana Regina de Aguiar; Barreto, Amanda Blanco Gomes; Hoffmann, Michelle Cristina F. R.; Cubas, Anelise Leal Vieira (Revista Brasileira de Meio Ambiente & Sustentabilidade, 2021)
ABSTRACT Food waste is generated in restaurants along with other forms of waste resulting from preparation of meals. Several entities are responsibility for the waste generation including manufacturers, importers, distributors, traders, individuals and service providers for the management of municipal solid waste, in accordance with the Brazilian National Solid Waste Policy (SWP). Thus, it is essential to understand the relevant socio-environmental, legislative and economic issues in order to seek alternatives aimed at the prevention, reduction and correct disposal of food waste. Reverse logistics is an important tool that can help in dealing with food waste. In this context, the objective of this study was to apply reverse logistics as a strategy to minimize and add value to restaurant waste. The methodological procedures involved a field study in a restaurant located in the city of Florianópolis, in southern Brazil. As a result, a guiding framework was developed for restaurant owners to assist them in the implementation of reverse logistics. In addition, the study contributes to achieving the UN Sustainable Development Goals (SDGs/Agenda 2030), in particular SDG 2 (zero hunger) and 12 (sustainable agriculture and responsible consumption and production).